Síntese, caracterização e estudo interativo com DNA de meso-tetra(1-naftil)porfirinas e seus complexos - Silveira, Carolina Hahn da (2018)
This study aimed to synthesize meso-tetra(1-naphthyl)porphyrin and its metalloporphyrin derivatives with metals of the first transition series (ZnII, CuII, NiII, CoIII, MnIII). The compounds were characterized by elemental analysis, mass spectrometry, 1H e 13C nuclear magnetic resonance, electron spectroscopy in ultraviolet- visible and infrared regions, fluorescence emission spectroscopy and cyclic voltammetry. In addition, studies of porphyrin aggregation in solution, photostability, singlet oxygen generation and theoretical calculations by DFT were also evaluated. The interaction of the porphyrin compounds with the ct-DNA were evaluated for experimentally (via UV-vis and emission spectroscopy) and through molecular docking. In both, the ability of the derivatives to establish interactions was observed, with the main binding forces being the Van der Waals interactions and hydrophobic interactions. In addition, the previous photodynamic activity of these compounds against microorganisms was also evaluated.